Processes of subjectification through students’ teamwork – openings for sound professional judgment - Kathrine R. Tvinnereim; Marit Heldal; Gry Mette D. Haugen; Merete Moe (Uniped)
The study was carried out at an early childhood education and care (ECEC) teacher education campus, where the students are future ECEC teachers and leaders of teams. The purpose of the study was to investigate how practice-oriented training (POT) in student teams could contribute to the students’ processes of subjectification as leaders and team members. The research question was How can practice-oriented training, with an emphasis on metacommunication and reflection, contribute to students’ subjectification processes? Based on the POT, the students wrote individual reflection papers, which served as the empirical material for the researchers. Looking for events and reflections related to processes of subjectification, the papers were analysed over the course of several working seminars. The analysis revealed three dimensions: i) re-orienting one’s own roles; ii) critical self-reflection, inner dialogues, and communication in teams; and iii) significance of silence. The results indicate that working with practice-oriented cases in student teams provides students with experience in listening to their team members, using metacommunication, discussing professional challenges in teams, and becoming more aware of roles as leaders and team members. The study points to the importance of the relational work in teams and suggests that ECEC teacher education should emphasise practical experience in order to support students’ development of sound professional judgement, subjectification and acknowledgment that the ECEC teacher and leader roles need to be changeable in a world not-yet-known.